Assessment and improvement of rainfall environment reproduction for climatic wind tunnel - Yingchao Zhang; Jinji Li; Zhe Zhang; Weiping Yuan; Jialong Zhou; Chun Shen; Chengchun Zhang (Engineering Applications of Computational Fluid Mechanics)
The climatic wind tunnel (CWT) is widely recognised as the optimal experimental environment for studying vehicle rainwater management, while the rainfall field generated by the CWT for vehicles may differ from the natural rainfall patterns. Therefore, this study aims to provide an approach to ensure consistency between the two rainfall environments by developing a virtual CWT (VCWT) rainfall scenario and a natural rainfall scenario. Two-phase flow computational fluid dynamics (CFD) method is conducted to reproduce the natural and CWT rainfall scenarios. Results of flow and rain fields of simulations are validated with experiment data respectively. Distributions of water film on the body surface and raindrop particles around the vehicle are discussed. The arrangement of rain spraying nozzles is optimised by assessing and analysing the discrepancy between the two rainfall scenarios so that a more rational rainfall environment can be provided in CWT. Improving the spacing and spray direction of nozzles benefits in narrowing the gap between natural and VCWT rainfall scenarios. An efficient approach is proposed in this work to make it possible to achieve the consistency between the rainfall environment in the CWT and the natural rainfall situation, providing an advance for rainwater management of vehicles.